STRATEGI DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI RIAU DALAM MENINGKATKAN MINAT BACA MASYARAKAT RIAU DI PERPUSTAKAAN SOEMAN HS TAHUN 2018 - Ghazli, Dimas Aryo; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Reading interest is one of the work programs of library development carried out by the Riau Province Library and Archives Office in the 2014-2019 RPJMD. In the library development work program, among others, organizing reading interest competitions, developing reading interest and culture, promoting libraries and film screenings, workshops for reading and writing, revitalizing libraries or mobile libraries, and so on are still not maximized due to various factors declining. . This research is motivated by how the strategy of the Riau Provincial Library and Archives Service in increasing people's interest in reading. The purpose of this research is to analyze the problems that occur in the implementation of the strategy which causes a decrease in the number of visitors in the HS Soeman Library. The method used in this research is descriptive method with qualitative research type. The types of research data are primary data and secondary data. Data collection techniques in this study were documentation and interviews. The data analysis technique used is descriptive qualitative data analysis.The results showed that increasing interest in reading carried out by the Department of Library and Archives of Riau Province has not been optimal. This can be seen from the decline in the number of visitors at the HS Soeman Library. There are inhibiting factors both from an internal and external perspective; provision of inefficient facilities and infrastructure and poor coordination. The right solution to solve the problem of increasing reading interest in the Soeman Hs Library is to create a tidier and more effective program planning and create policies that can improve coordination between each person in charge in each section concerned and the community, increase the budget, and increase reading interest. more intensive and routine. Keywords: Strategy, Reading Interests, Dipersip